DEVELOPMENT OF CAREER GUIDANCE MODUL FOR INCREASING YOUTH ENTERPRENEURSHIP - Tri Na'imah; Pambudi Rahardjo (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2012)
This study aimed to analyse career guidance model that had been applied by career guidance teachers;to analyse the weaknesses and strengths of the career guidance model; and to arrange career guidancemodel to increase youth enterpreneurship. This study used developmental research approach. First stepwas survey research with qualitative approach. Research location was determined purposively inPurwokerto. Data collecting employed interview and focus group discussion (FGD). Data analysis usedinteractive analysis model through stages of data reduction, data presentation, and verification.The results are: first, the model used for career guidance consists of: 1) material preparation of careerguidance in the form of practical work, about the preparation of the future relating to the continuationÂ of students both study and career plans and information about entering the workforce. 2) Method ofgiving guidance to the lectures, discussions, and assignments. 3) Media using the guidance in the form ofdrawings and graphic media liflet and film media. 4) Evaluation carried on by non-test techniques andtest the process and the guidance. Second, the model has practical advantages because the material isso easily accepted by students, using the method of assignment, so memandirikan students, using avariety of media to improve the quality of service, the evaluation was conducted in an integratedmanner between the test and the non-test techniques. However, the model also has a weakness formore career guidance materials to prepare students as workers, not entrepreneurs. The method has notbeen a comprehensive career guidance and less participatory. Comprehensive evaluation of theguidance is also less, because there is no evaluation of the program. There has been no follow-upactivities of guidance activities, the career counseling. Third, the design of career guidance modules thatcan enhance students' entrepreneurial spirit contains material about self awareness, HARRY JOEWINDOW,career decisions with SWOT analysis, self-employment psychological characteristics, selfmotivation,creativity development. The method used discussion, reflection, succes story, theassignment independently.